817 Potent P2Y12 inhibitors in elderly population, insigth from praise registry. (8th December 2021) - Elia, Edoardo; D'Ascenzo, Fabrizio; Breviario, Susanna; Bruno, Francesco; Marengo, Giorgio; De Filippo, Ovidio; Conrotto, Federico; Maria De Ferrari, Gaetano
Abstract: Background: The safety and efficacy of potent P2Y12 inhibitors (Ticagrelor and Prasugrel) in dual antiplatelet therapy (DAPT) with aspirin in elderly patients with acute coronary syndrome (ACS) remains unclear. Methods: All ACS patients aged 75 years and older treated with Percutaneous Coronary Intervention (PCI) from PRAISE dataset were included. The safety and efficacy of Ticagrelor vs Clopidogrel was evaluated with inverse probability of treatment weighting (IPTW). Sensitivity analysis was performed for patients older or equal than 85 years old. All-cause mortality was the primary endpoint, while myocardial infarction (MI), Bleeding Academic Research Consortium (BARC) 3-5 bleedings and Major and Net Adverse Clinical and Cardiac Events (MACE and NACE) were the secondary ones. Results: 4287 patients were included, 3197 treated with Clopidogrel and 1090 with Ticagrelor. After 16±3 months, Ticagrelor showed neutral effect on NACE and mortality (HR 0.98; 0.63-1.52, p=0.94 and HR 0.38; 0.14-1.04, p=0, 06), reduced risk of MACE and MI (HR 0.82; 0.23-0.91, p=0.03 and HR 0.43; 0.14-0.89, p=0.04) and increased risk of BARC 3-5 bleeding (HR 2.14; 1.19-3.85, p=0.001). In very elderly patients (≥85 years) Ticagrelor decreased risk of MI and increased risk of bleeding (HR 0.69; 0.22-0.95, p=0.04 and HR 2.36; 1.02-5.52, p=0.04, all 95%CI) with neutral effect on NACE and MACE. Conclusions: In elderly ACS patients treated with PCI, Ticagrelor was associated with neutral effect on all-cause mortality, lower risk MACE and MI compared with Clopidogrel. Such benefit was counterbalanced by increased risk of major bleedings. These results were consistent among patients aged 85 years and older.